The alpha and the omega (6 lipids): discovering dietary drivers of heterotopic ossification - Peyton L. Carpen; Matthew B. Greenblatt (Journal of Clinical Investigation, 2026)
Bone formation in soft tissues, known as heterotopic ossification (HO), can occur as a complication of trauma or burn injury and can cause pain and functional limitations in the affected site. HO remains an unmet clinical challenge due to a general lack of specific medical therapies. In this issue of the JCI , a study by Moye et al. identified obesity as a risk factor for HO and further found that the association with obesity was driven not by caloric surplus, but instead by dietary omega-6 lipids, which are characteristically elevated in the Western diet. These omega-6 lipids accumulated directly at the incipient HO site, where they served as substrates for prostaglandin E 2 (PGE 2 ), fueling aberrant osteoblast differentiation. Overall, this work provides compelling support for dietary intervention or pharmacologic therapy directed at downstream PGE 2 signaling as approaches to reduce HO in at-risk patients.